(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
This article discusses the challenges and issues related to the development of the knitting industry in Uzbekistan. It highlights the existing obstacles, including resource limitations, technological constraints, and market dynamics, while also exploring potential strategies for addressing these challenges. The study emphasizes the importance of innovation, modernization of equipment, and the integration of sustainable practices to enhance the competitiveness of the knitting sector in both domestic and international markets. By analyzing current trends and providing practical recommendations, this research aims to contribute to the growth and advancement of the textile and garment industries in Uzbekistan.